Are public open space attributes associated with walking and depression?. (April 2018) - Koohsari, Mohammad Javad; Badland, Hannah; Mavoa, Suzanne; Villanueva, Karen; Francis, Jacinta; Hooper, Paula; Owen, Neville; Giles-Corti, Billie
Abstract: Public open spaces (POS) are key neighbourhood destinations shown to confer numerous physical and mental health benefits. The amount and spatial distribution of POS throughout cities are guided by urban planning policies and standards. However, empirical evidence is not generally used to create POS standards. Developing and testing POS indices associated with positive health outcomes, can inform evidence-based POS urban design and planning standards that support the creation of healthier cities. This study examined associations of urban design policy-derived and empirical measures of POS proximity and density with walking and depression. The 2011–12 Australian Diabetes, Obesity and Lifestyle study (AusDiab) wave data were used. Adults living in metropolitan Melbourne, Australia were included ( n = 319). Participants reported walking for recreation and any walking within their neighbourhood during the last week. Depression was calculated using the Center for Epidemiologic Studies Short Depression Scale (CESD-10). Informed by Australian urban design policies and empirical evidence, various POS measures were calculated at different street network distances around residential addresses using geographic information systems software. Measures tested included: distance to nearest POS, size of nearest POS, total number of POS, and area of POS at scales of 400, 800, 1000, and 1600 m. Associations of these POS measures with walking and depression were examined using adjusted multilevel logistic regression models. Overall 68% and 77% of participants reported walking for recreation and any walking in the past week, respectively; and about 13% were categorized as depressed. Living within 400 m of POS was not associated with either type of walking, but those whose nearest POS was > 1.5 ha had 1.90 and 2.66 times greater odds of walking for recreation and any walking during the last week, respectively. In Melbourne, the urban design policy standard is that POS be available within 400 m of homes. In our study, this standard was not associated with walking or depression; however having a larger POS nearby supported residents' walking. This study highlights the importance of assessing such standards for their potential health impact, and warrants further investigation. Highlights: The size of public open space was associated with residents' walking. Living within 400 m of public open space was not associated with residents' walking. None of public open space measures were associated with depression.